2007
DOI: 10.1039/b707306m
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface active solutes on bubbles in an acoustic field

Abstract: The interaction between gas bubbles and ultrasound in water leads to acoustic cavitation under specific experimental conditions. Acoustic cavitation has been used in a number of areas, these include therapeutic applications, contrast imaging, synthesis of nanomaterials, production of nanoemulsions, treatment of food materials, waste-water treatment, etc. In all these applications, a variety of chemical species are present and most of these chemicals are surface active in nature. There is limited literature ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 95 publications
0
40
0
Order By: Relevance
“…[ 14 ] In general, the adsorption of surface-active solutes onto the bubble surface retards bubble coalescence. [ 15 ] Within the limitations of the measurement method and the systems studied, bubble coalescence does not appear to be dependent on the (2004)(2005) and an Incoming Marie-Curie fellow (2005)(2006)(2007). His research activities include the study of the non-equilibrated interfaces, synthesis of nanomaterials with new properties in the ultrasonic cavitation zone, development of nanocontainers with multifunctional shells, and controlled permeability.…”
Section: Mechanism Of Cavitation and Collapse Near Solid Surfacesmentioning
confidence: 99%
“…[ 14 ] In general, the adsorption of surface-active solutes onto the bubble surface retards bubble coalescence. [ 15 ] Within the limitations of the measurement method and the systems studied, bubble coalescence does not appear to be dependent on the (2004)(2005) and an Incoming Marie-Curie fellow (2005)(2006)(2007). His research activities include the study of the non-equilibrated interfaces, synthesis of nanomaterials with new properties in the ultrasonic cavitation zone, development of nanocontainers with multifunctional shells, and controlled permeability.…”
Section: Mechanism Of Cavitation and Collapse Near Solid Surfacesmentioning
confidence: 99%
“…In our previous work, it was observed that the extent of stable/transient cavitation could be manipulated by placing a thin film at the air-solution interface using SL as a probe. 8 The previous studies undoubtedly have shown that the relationship between SL and SCL is dependent upon several experimental parameters. In order to expand this knowledge base, a systematic investigation has been carried out to study the behaviour of SL and SCL bubbles at three different frequencies and different power levels in the absence and presence of a lid at the air-solution interface.…”
Section: Resultsmentioning
confidence: 99%
“…7 Like SCL, SL can also be used to probe cavitation structures and to quantify the cavitation activity. 8 Our recent studies have shown that SL and SCL probe different bubble populations. 10,11 We have also reported that SL bubbles may be hotter than SCL bubbles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bubbles disintegrate into fragments due to the violent nature of the collapse. In stable cavitation however, bubble growth occurs over thousands of acoustic cycles either by rectified diffusion and/or bubble coalescence pathways [8]. Stable cavitation is commonly observed at high (> 200 kHz) ultrasound frequencies.…”
Section: Introductionmentioning
confidence: 99%